Cross Sectional Study: Cigarette Smoking and the Usage of Ecigarettes Among the Students of University of Cyberjaya - Aizat Helmi Ali; Ibrahim Mukhlis Mohamad Azam; Nurul Nabilah Yusof; Salasawati Hussin (Asian Journal of Medicine & Health Sciences, 2022)
Background: Electronic cigarettes continue to grow and gain popularity, recognition and acceptance globally, especially among adolescents. Aside from that, more adults are switching from smoking to vaping due to their disproportionate misconceptions pertaining to the adverse effects of the practices respectively. Therefore, this study aims to assess the association between e-cigarettes use and cessation of smoking. Materials and Methods: A cross-sectional study was conducted among 145 students in the period from November 2020 until January 2021 in University of Cyberjaya (UOC), Cyberjaya, Selangor, Malaysia. The sample selection was done by convenience sampling and voluntary participation. The self-administered questionnaire was distributed online. Result: The prevalence of smokers and vapers among the students are 15.9% and 12.4% respectively. Most of the smokers started smoking due to friend influence (26.7%). For vapers, most of them start using vape to quit using tobacco products (38.9%). Prevalence of smoking and vaping was significantly higher in male (p = 0.003, p = 0.007). There is a significant association between usage of e-cigarette and cessation of cigarette smoking (p = 0.001). Most vapers believe that e-cigarette is less harmful when compared to smoking tobacco (61.1%). Conclusion: This study found that 15.9% and 12.4% students are smokers and vapers respectively. Males’ students were more likely to smoke and vape. E-cigarette use appears to be associated with smoking cessation, even so, most of them believe e-cigarettes are safer than tobacco smoking. Hence, further study on the use of e-cigarettes and its effect on human health should be conducted to create awareness about the danger of it.